The importance of road transport infrastructure development and maintenance in trade facilitation : a South African case - Kgamanyane, Moeti (GSB: Faculty, 2016)
Road transportation is the most frequently used means of transporting goods and people in much of sub-Saharan Africa. Furthermore, because of the region's geographic nature, where many of the countries are landlocked, imports and exports of goods happen primarily by land and in this case by road transport. This is primarily due to the fact that other means of surface transportation like rail and navigable rivers are not well developed. Nonetheless, the lack of complementarity between the two land transportation modes, that is rail and road, has led to the over usage of the road. This has invariably led to congestion and deterioration of the road network with minimal investment in both the development and maintenance of the road infrastructure. Though there is an acknowledgement of this problem and attempts to address it through efforts like the Programme for Infrastructural Development in Africa (PIDA), and regionally in SADC thorough the adoption of the SADC Regional Infrastructure Development Master Plan Vision 2027 (RIDMP), much effort still needs to be put within individual countries to develop and maintain primary road networks that are able to connect to regional trade corridors.